2010
DOI: 10.1097/brs.0b013e3181c838cc
|View full text |Cite
|
Sign up to set email alerts
|

Minimizing Ferromagnetic Artefact With Metallic Lumbar Total Disc Arthroplasty Devices at Adjacent Segments

Abstract: Relatively simple modifications to MRI parameter settings can be made on conventional high field-strength (1.5T) closed-bore scanners, which minimize metal artefact and enhance imaging of adjacent segments with ferromagnetic TDA devices. Such modifications effectively match appearances to those obtained with outmoded low field-strength (0.3T) open-bore scanners.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 7 publications
1
5
0
Order By: Relevance
“…Antosh et al 27 , demonstrated a reduction in artifacts following implantation of cobalt-chromium PCM (NuVasive, Inc., USA) and Prodisc-C (Synthes Spine, USA) prostheses by using a 0.2 T MRI. Similar data were obtained in the evaluation of adjacent segments after total arthroplasty of the lumbar spine using an MRI tomograph with a magnetic field strength of 0.3 T. 28 As one might suspect, a 3 T magnet MRI had worse artifact production following implants than 1.5 T magnets. 29 In addition, the direction of frequency encoding, slice thickness, throughput, and echo time also affect the severity of artifacts.…”
Section: Limitationssupporting
confidence: 64%
“…Antosh et al 27 , demonstrated a reduction in artifacts following implantation of cobalt-chromium PCM (NuVasive, Inc., USA) and Prodisc-C (Synthes Spine, USA) prostheses by using a 0.2 T MRI. Similar data were obtained in the evaluation of adjacent segments after total arthroplasty of the lumbar spine using an MRI tomograph with a magnetic field strength of 0.3 T. 28 As one might suspect, a 3 T magnet MRI had worse artifact production following implants than 1.5 T magnets. 29 In addition, the direction of frequency encoding, slice thickness, throughput, and echo time also affect the severity of artifacts.…”
Section: Limitationssupporting
confidence: 64%
“…The decreased UA‐RI at the placental site whereas SA‐RI remains constant may reflect the local development of the shunts at the placental site such as between spiral artery and intervillous space, because a lower RI in the more distal part of the uteroplacental circulation indicates the development of such shunts. However, this suggests the possibility that the UA‐RI was not affected because the change in UA‐RI is a local event 11 , 31 33 . However, future studies are needed to determine the relationship between the Doppler spiral artery resistance and histological features of vascular remodeling.…”
Section: Discussionmentioning
confidence: 99%
“…All follow-up MRIs and > 90% of pre-treatment MRIs were from 1.5 T units. Metal artefact reducing techniques [13] were used on 97% of follow-up MRIs and implied thin slices (3 mm) and increased pixel bandwidth (BW), echo train length (ETL) and number of excitations (NEX). These follow-up MRIs included (a) sagittal T2-weighted FSE images: repetition time (TR) / echo time (TE), 4480-5000 ms / 92-94 ms; matrix 448x448; BW 413; ETL 30; NEX 3, (b) sagittal T1-weighted FSE images: TR / TE, 549-610 ms / 8 ms; matrix 448x448; BW 698; ETL 7; NEX 4, and (c) axial T2-weighted FSE images: TR / TE, 4201-5190 ms / 72-92 ms; matrix 320x320 or 512x512; BW 390-413; ETL 20; NEX 2-3.…”
Section: Mri Evaluationmentioning
confidence: 99%